A model based study on the dynamics of COVID-19: Prediction and control. (July 2020) - Mandal, Manotosh; Jana, Soovoojeet; Nandi, Swapan Kumar; Khatua, Anupam; Adak, Sayani; Kar, T.K.
Highlights: A mathematical model has been proposed to analyse the pandemic COVID-19. The model has been analysed both theoretically and numerically. The procedure to control the basic reproduction number R 0 has been provided. We have formed an optimal control problem where governmental policy is the control. The model is used for short term prediction of COVID-19 in three states of India. Abstract: As there is no vaccination and proper medicine for treatment, the recent pandemic caused by COVID-19 has drawn attention to the strategies of quarantine and other governmental measures, like lockdown, media coverage on social isolation, and improvement of public hygiene, etc to control the disease. The mathematical model can help when these intervention measures are the best strategies for disease control as well as how they might affect the disease dynamics. Motivated by this, in this article, we have formulated a mathematical model introducing a quarantine class and governmental intervention measures to mitigate disease transmission. We study a thorough dynamical behavior of the model in terms of the basic reproduction number. Further, we perform the sensitivity analysis of the essential reproduction number and found that reducing the contact of exposed and susceptible humans is the most critical factor in achieving disease control. To lessen the infected individuals as well as to minimize the cost of implementing government control measures, we formulate an optimal control problem, and optimal control is determined. Finally, we forecast a short-term trend of COVID-19 for the three highly affected states, Maharashtra, Delhi, and Tamil Nadu, in India, and it suggests that the first two states need further monitoring of control measures to reduce the contact of exposed and susceptible humans.